Evaluación de la resistencia a manchas foliares en 19 accesiones de maíz (Zea mays L.) suave y duro, en la localidad de Guaranda en su segundo periodo de validación - Saltos Saltos, Fernanda Yessenia (2022)
One of the most produced and consumed cereals worldwide is corn, as it is used mainly as a source for both human and animal food, it is also considered as a source of raw material for industrial uses, with the Bolívar Province being one of the most important in the production of this cereal in the sierra region, cultivating approximately 23,000 ha of floury white maize. In recent years, due to monoculture and constant climate change, farmers have been affected by the severity of the presence of the asphalt spot complex, since if the disease appears at an early stage (flowering), considerable yield losses can occur, in a range from 30% to 100%. The present investigation was carried out at the Laguacoto III Farm of the State University of Bolívar, being the second year of implementation because it is of great importance to find materials that are resistant or tolerant to most leaf spots that reduce the productivity and profitability of the farmer, at the same time providing them with an alternative to reduce the costs of the inputs used to control these diseases. The stated objectives were: i) To evaluate the resistance to leaf spots in 19 accessions of soft and hard corn in the town of Guaranda in its second validation period. ii) Determine the incidence and severity of leaf spots in maize crops. iii) Select the best soft and hard maize accessions for this agro-ecological zone in relation to their response to leaf spots. A randomized complete block design (DBCA) was applied with 19 treatments (soft and hard maize accessions) and three repetitions, Analysis of Variance (ADEVA), Tukey's Test at 5% was performed to compare the means of the treatments, Correlation and linear regression. The response of soft and hard maize accessions for the main agronomic components and morphological descriptors was very different. It was confirmed in the second year of this research that there was a strong genotype-environment interaction between the treatments, the crop cycle, the incidence and severity of the leaf spot complex and the yield components, obtaining better results in the varieties released by INIAP. and the Criollo Phenotype of Chimborazo showing a better adaptability to this agroecological zone for being moderately precocious, but being affected by climate change due to periods of rain and untimely winds, a reduction in yield was seen due to large percentages of stem lodging. and root, ear health, percentage of plants without ear. Finally, this research made it possible to find alternatives that contribute to improving the good living of farmers in the province, providing data on various promising accessions with very good results.